An association study between Heme oxygenase-1 genetic variants and Parkinson's disease - Ayuso, Pedro; Martínez, Carmen; Pastor, Pau; Lorenzo-Betancor, Oswaldo; Luengo, Antonio; Jiménez-Jiménez, Félix J.; Alonso-Navarro, Hortensia; Agúndez, José A. G.; García-Martín, Elena (Frontiers in Cellular Neuroscience, 2014)
Abstract The blood-brain barrier (BBB) supplies brain tissues with nutrients, filters harmful compounds from the brain back to the bloodstream, and plays a key role in iron homeostasis in the human brain. Disruptions of the BBB are associated with several neurodegenerative conditions including Parkinson’s disease (PD). Oxidative stress, iron deposition and mitochondrial impaired function are considered as risk factors for degeneration of the central nervous system. Heme oxygenase (HMOX) degrades heme ring to biliverdin, free ferrous iron and carbon monoxide being the rate-limiting activity in heme catabolism. The isoform HMOX1 is highly inducible in response to reactive oxygen species which induce an increase in BBB permeability and impair its pathophysiology. Consequently, an over- expression of this enzyme may contribute to the marked iron deposition found in PD. We analyzed common HMOX1 gene variants in 691 patients suffering from PD and 766 healthy control individuals. Copy number variations in the HMOX1 gene exist, but these do not seem to be associated with PD risk. In contrast two polymorphisms that modify the transcriptional activity of the gene, namely a VNTR (GT)n and the SNP rs2071746, are strongly associated with PD risk, particularly with the classic PD phenotype and with early onset of the disease. This study indicates that HMOX1 gene variants are associated to the risk of developing some forms of PD, thus adding new information that supports association of HMOX gene variations with PD risk.